Dispatching of distribution networks with high permeability distributed new energy based on phase shifting transformer loop-closing device - Xiaochen, Gao; Haoran, Xu; Xin, Zhao; Shan, Gao; Haixiang, Xie; Ningyu, Zhang; Qun, Li; Yue, Yang (Frontiers in Energy Research, 2025)
To address the issue of curtailment in wind and photovoltaic power due to high penetration of distributed renewable energy sources in multi-partition distribution networks, and to enhance operational efficiency and voltage quality, a day-ahead and intra-day scheduling strategy based on Phase Shifting Transformer (PST) loop-closing device is proposed. The day-ahead scheduling model aims to maximize the benefits from loop-closing operations by incorporating errors from new energy and load forecasts. Robust optimization techniques are employed to solve this model, resulting in the determination of the optimal loop-closing line. For intra-day scheduling, the focus is on minimizing the weighted sum of curtailment rate, voltage deviation rate, and network loss, thereby optimizing reactive power distribution and ensuring full utilization of renewable energy. Second-order cone programming is applied to the objectives and constraints to ensure convergence and expedite the solution process. Simulation results on an improved IEEE 33 bus test system demonstrate that the proposed day-ahead and intra-day scheduling strategy effectively leverages the voltage regulation and power flow control capabilities of PST loop-closing devices. This approach not only ensures the safety of the distribution network but also facilitates cross-regional integration of distributed renewable energy, reduces operational costs, and enhances overall network performance.